Association between small dense LDL levels and hepatic fibrosis in patients with nonalcoholic fatty liver disease. Issue 37 (16th September 2022) - Young Kim, Sun; Mun, Subin; Yu, Jung Hwan; Jin, Young-Joo; Ju Suh, Young; Cho, Sang-Heon; Lee, Jin-Woo
Abstract : While patients with nonalcoholic fatty liver disease (NAFLD) continue to increase worldwide, few hematological biomarkers are helpful. This study examined the potential of small dense low density lipoprotein (sdLDL) as a noninvasive biomarker for NAFLD and investigated the relevance of liver fibrosis. One hundred seventy two patients were enrolled: 121 NAFLD patients and 51 healthy controls. The lipoprotein profiles of NAFLD patients and controls were analyzed, and transient elastography (Fibroscan®) was performed to evaluate the degree of NAFLD. The liver biopsy results in some NAFLD patients were also analyzed. Age-gender matching was performed among the 172 patients, and a comparison with 46 NAFLD patients with the control group confirmed that the sdLDL ( P  < .001) is significantly higher in the NAFLD group. A liver fibrosis test performed on 121 NAFLD patients confirmed a positive correlation between the degree of hepatic fibrosis and the sdLDL/LDL ratio ( R  = 0.215, P =  .017). The area under the curve of the sdLDL for the diagnosis of NAFLD was 0.734 (95% CI, 0.631–0.838), and the area under the curve of the sdLDL/LDL ratio was 0.730 (95% CI, 0.621–0.829). The sdLDL and NAFLD activity scores of the 11 NAFLD patients who underwent liver biopsy showed a positive correlation, but it was not statistically significant. The sdLDL was higher in NAFLD patients than in controls and showed a tendency to increase gradually with increasing degree of hepatic steatosis and fibrosis. In particular, the sdLDL/LDL ratio showed a significant correlation with the degree of hepatic fibrosis, and the sdLDL measurement could be useful in NAFLD patients.